THE EFFECT OF INQUIRY-BASED LEARNING ON STUDENTS’ CRITICAL THINKING IN READING - Wahab, Abdul; Terasne, Terasne (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
This research was aimed to find out the significant effect of Inquiry-Based Learning on students? critical thinking in reading at third-semester students of  Faculty of Education, and Education of Science Qamarul Huda University, Bagu, Central Lombok in academic year 2019/2020. This research was experimental research that categorized by pre-experimental One Group Pretest-Posttest design. The population of this research was at third-semester students of  Faculty of Education, and Education of Science Qamarul Huda University, Bagu, Central Lombok which consisted of 18 students and using surfeited sampling. The instrument of collecting the data was used multiple-choices and questionnaires. In this research, the writer rendered treatment and prepared a test in the form of multiple-choices to look the effect of Inquiry-Based Learning and questionnaires for look the critical thinking. The result of data analysis indicated at third-semester students of Faculty of Education, and Education of Science Qamarul Huda University, Bagu, Central Lombok attained high score on post-test whom were treated by Inquiry-Based Learning. It means that Inquiry-Based Learning gave a significant effect on critical thinking of students in reading. It was proven by the lowest and highest in pre-test score was 30 and 50 and post-test was 35 and 65. Then, the result of hypothesis testing was the alternative hypothesis accepted. It was provable that t-test was higher than t-table, which was the score of t-test was 3.81 and t-table in df 17 with significant 0.05 was 1.753.